2021
DOI: 10.1186/s12909-021-02661-4
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in Spanish medical students

Abstract: Background Burnout syndrome is a frequent syndrome related to people that feel a deterioration in their daily activities due to highly demandant psychological requirements in their workplaces. Within last decades, this syndrome has been studied across medical professionals, concluding that stress levels that physicians suffer is high enough to make them develop burnout syndrome. In the case of medical students, there are some recent studies, although with small samples. For this reason, given t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
(22 reference statements)
1
11
1
5
Order By: Relevance
“…Levels of the various burnout dimensions in our sample showed higher levels on professional emotional exhaustion and depersonalisation/cynicism than in a meta-analysis among medical students, but no difference on personal accomplishment [ 17 ]. Conversely, levels of academic emotional exhaustion and depersonalisation/cynicism were lower in our sample than in a Spanish study among medical students, but again showed no differences in personal accomplishment [ 42 ]. Considering limitations of cultural differences and that these comparison studies were conducted outside of the context of COVID-19, it may be prudent to conclude that the professional burnout dimensions of emotional exhaustion and depersonalisation/cynicism are relatively high in our study, and that academic burnout dimensions of emotional exhaustion and depersonalisation/cynicism are relatively low.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Levels of the various burnout dimensions in our sample showed higher levels on professional emotional exhaustion and depersonalisation/cynicism than in a meta-analysis among medical students, but no difference on personal accomplishment [ 17 ]. Conversely, levels of academic emotional exhaustion and depersonalisation/cynicism were lower in our sample than in a Spanish study among medical students, but again showed no differences in personal accomplishment [ 42 ]. Considering limitations of cultural differences and that these comparison studies were conducted outside of the context of COVID-19, it may be prudent to conclude that the professional burnout dimensions of emotional exhaustion and depersonalisation/cynicism are relatively high in our study, and that academic burnout dimensions of emotional exhaustion and depersonalisation/cynicism are relatively low.…”
Section: Discussioncontrasting
confidence: 73%
“…Levels of academic burnout were more moderate. A comparison with a study conducted in 2019, using the MBI-SS scale among medical students in Spain (no comparison in Belgium available) showed significantly lower rates of academic burnout in our sample than in the Spanish sample for EE ( n = 1073, M = 27.50 ± 7.16, t (1265) = -15.81, p < 0.001), for DP/CY ( n = 1073, M = 14.83 ± 7.09, t (1265) = -6.35, p < 0.001), but again showed no significant differences for PA ( n = 1073, M = 22.38 ± 6.89, t (1265) = -0.51, p = 0.61) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are also in consonance with studies previously reported in other cultural environments. Gil-Calderon and colleagues reported in Spanish medical students that family support is linked to lower scores on burnout measures [38]. In the United States, a positive family environment has been described as a source of happiness and a pleasant home atmosphere that allows medical students to relax from rigorous study, evaluations, and stressful clinical scenarios [39].…”
Section: Positive Correlation Between Burnout and The Measures Of Lon...mentioning
confidence: 99%
“…The importance of planning days devoted to rest and contact with other people, including those outside one’s professional circles, has been emphasized [ 29 ]. In addition, the results of research conducted in this area allow us to provide the following suggestion: information about the causes of burnout and methods of dealing with it should be introduced at the stage of preparation for the medical profession [ 24 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%